PENGGUNAAN INSTRUMEN ASESMEN OTENTIK DALAM PEMBELAJARAN MEMBACA KRITIS TEKS EKSPOSISI PADA SISWA SMK DI BIMA - Arwan Arwan (Center of Language and Cultural Studies, 2018)
This study aims to identify the authentic assessment forms used in learning critical reading of texts exposition. In this research, using qualitative methods with this kind of phenomenology. The results of this research is the description of the form of the process assessment and the results assessment are used in learning to read critically of exposition text. The process assessment in the form of a attitude journal to know the attitude of learners in learning. Indicators in this attitude journal included spiritual attitudes and social attitudes. the results assessment in the learning are used to determine the success of learners in understanding of exposition text. The assessment instrument made corresponding with SK, KD, and indicators of learning. The use of authentic assessment is impressive in learning to read critically is not implemented by all teachers. Understanding of learners tend to be determined globally.